Proceedings of the 25th Annual Congress of the International Liver Transplantation Society. Issue 8 (August 2020) - Chadha, Ryan; De Martin, Eleonora; Kabacam, Gokhan; Kirchner, Varvara; Kalisvaart, Marit; Goldaracena, Nicolas; Tanaka, Tomohiro; Spiro, Michael; Sapisochin, Gonzalo; Vinaixa, Carmen; Hessheimer, Amelia; Campos Varela, Isabel; et al.
Abstract : The 25th Annual Congress of the International Liver Transplantation Society was held in Toronto, Canada, from May 15 to 18, 2019. Surgeons, hepatologists, anesthesiologists, critical care intensivists, radiologists, pathologists, and research scientists from all over the world came together with the common aim of improving care and outcomes for liver transplant recipients and living donors. Some of the featured topics at this year's conference included multidisciplinary perioperative care in liver transplantation, worldwide approaches to organ allocation, donor steatosis, and updates in pediatrics, immunology, and radiology. This report presents excerpts and highlights from invited lectures and select abstracts, reviewed and compiled by the Vanguard Committee of International Liver Transplantation Society. This will hopefully contribute to further advances in clinical practice and research in liver transplantation.